261 GENDER DIFFERENCE IN THE IMPACT OF MULTIPLE CARDIOVASCULAR RISK FACTORS ON THE FEMORAL ARTERY INTIMA-MEDIA THICKNESS IN ASYMPTOMATIC YOUNG ADULTS: THE BOGALUSA HEART STUDY. (1st January 2006) - Paul, T. K.; Srinivasan, S. R.; Jackson, S. A.; Raggi, P.; Chen, W.; Berenson, G. S.
Abstract : Background: Males in general are considered to have more peripheral arterial disease (PAD) than females. Manifestations of PAD in relation to cardiovascular risk factors have been studied by ultrasound-assessed femoral artery intima-media thickness (IMT), mainly in middle-aged and older men and women. However, little is known on the impact of risk factors on the femoral IMT in young adults by gender. This study examined whether gender influences the impact of multiple cardiovascular risk factors on the femoral artery IMT in asymptomatic young adults in a biracial (black-white) population. Methods: Femoral IMT was measured by B-mode ultrasonography in 1, 080 males and females (aged 24-43 years; 71%w hite, 43% male) who participated in the Bogalusa Heart Study. Results: Age-adjusted femoral IMT showed a gender difference (males > females, p = .0001). In a bivariate analysis adjusted for age and race IMT related significantly to BMI, waist circumference, systolic and diastolic blood pressures, LDL cholesterol, HDL cholesterol (inverse relation), total to HDL cholesterol ratio and triglycerides in females and only to systolic blood pressure and LDL cholesterol in males. In a multivariate model age, systolic blood pressure, cigarette smoking, and total to HDL cholesterol ratio related independently, in that order, to IMT in females and age and LDL cholesterol in males. In females, mean IMT increased with increasing number of risk factors defined as values above the age-, race-, and gender-specific 75th percentile of systolic blood pressure, waist circumference, total to HDL cholesterol ratio, and insulin along with positive smoking status (p for trend = .001), with respective mean IMT (mm) values of 0.61, 0.65, 0.72, and 0.77, for 0, 1-2, 3, and 4-5 risk factors. There was no such significant trend in males. Conclusions: Although males vs females had thicker IMT, the observed increasing trend of femoral IMT with increasing number of risk factors in asymptomatic young female adults suggests that females are relatively more susceptible in this regard than males. These results suggest that gender should be considered in risk profiling and interventions.